CHARACTERISTIC OF PEDIATRIC UROLITHIASIS PATIENTS IN ZAINOEL ABIDIN HOSPITAL - Yohanes, Simon Natanel; Dahril, Dahril (Indonesian Journal of Urology, 2018)
Objective: We conducted a study to describe the characteristics of pediatric urolithiasis patients in Zainoel Abidin Hospital, Aceh-Indonesia. Material & Methods: Between January 2013 and March 2016, we retrospectively reviewed the medical records of 16 pediatric patients with urolithiasis in Zainoel Abidin Hospital, Aceh-Indonesia. The patients were come from whole Aceh region and the variables are sex, age, family history of stone disease, and stone location. The data were described in graphics and tables. Results: From 16 pediatric urolithiasis patients, 9 patients (56.3%) were males and 7 patients (43.7%) were females. In 2013 there were 4 pediatric urolithiasis patients (1.2%), in 2014 there were 5 (1.6%), and in 2015 there were 3 (2.3%). From January – March 2016 there were 4 pediatric urolithiasis patients (4.5% of all urolithiasis patients). The mean age of all pediatric patients were 7.7 ± 5.5 years (1-17 years). The incidence of urolithiasis for group < 5 years of age were 6 patients (37.5%) with mean age of 2 ± 1.14 years (1-4 years), in 5–10 years age group, there were 4 patients (25.0%) with mean age 7 ± 2.16 years (5-10 years), and 11–18 years age group, there were 6 patients (37.5%) with mean age 13.8 ± 2.16 years (12-16 years). Stones were located in the upper urinary tract in 9 cases (56.3%), lower urinary tract in 6 cases (37.5%), and combine stone located in upper and lower urinary tract in 1 case (6.2%). There were 5 patients (31.3%) with family history of stone disease. Conclusion: Pediatric urolithiasis case in Aceh Province is slightly predominant in male children, with mean age of 7.7 ± 5.5 years (1-16 years). The most common age group is evenly distribute between <5 years old and 11-18 years old. The most common stone location is in the upper urinary tract.